UPAYA MEMAKNAI KEMBALI CITRA EKS BANDARA KEMAYORAN MELALUI GALERI EDUKASI AVIASI - Santosa, Aaron Pratama; Carina, Nina (Jurusan Arsitektur dan Perencanaan, 2025)
Kemayoran Airport, built in the 1930s and officially operational on July 8, 1940, is a historic airport that played a significant role in the development of aviation in Indonesia. Constructed by the Dutch East Indies government, it featured modern facilities comparable to European airports of its time. After undergoing various significant historical phases, including the Japanese occupation during the Asia-Pacific War and Indonesia's independence revolution, the airport continued to operate and evolve until its closure on March 31, 1985, due to limitations in accommodating rapid advancements in aviation technology, with the rise of wide-body aircraft and rapid population growth near Kemayoran airfield. Kemayoran Airport subsequently fell into neglect and was replaced by new infrastructure. The traces of Kemayoran Airport’s former glory have almost completely disappeared, rendering it a